SUBCRONIC TOXICITY TEST COMBINATION OF Phyllanthus niruri AND Centella asiatica EXTRACT AT HEMATOLOGY IN RATS - Siti Fatmawati Fatimah; Endang Darmawan; Iin Narwanti; Dzulhaifa Dzulhaifa; Ira Aprilia Wulandari; Ria Putri Salma (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: Meniran (Phyllathus niruri) and pegagan (Centella asiatica) are well-known medicinal plants in Indonesia. Uses of meniran and pegagan as herbal medicines need to be examined for their subchronic activity to assure their safety. Objective: This study aimed to evaluate subchronic effects of a combination of extracted meniran and pegagan on Wistar rats through haematological parameters (erythrocytes, haemoglobin, haematocrit, MCV, MCH, and MCHC).Methods: Animal models used were 56 male and female Wistar rats and were divided randomly into 4 groups. Group 1 received CMC-Na 1% (control group). Group 2 received extracts of meniran and pegagan (50:50 mg/kgBW). Group 3 received extracts of meniran and pegagan (250:250 mg/kgBW). Group 4 received extracts of meniran and pegagan (1250:1250 mg/kgBW). Subchronic test of meniran and pegagan was conducted by providing treatments for the Wistar rats for 28 days. Their haematological substances were analysed statistically by using one way ANOVA and Kruskal-Wallis method with confidence interval of 95% and post-hoc. Results: This study found that the haematological substances in male Wistar rats were normal and did not significantly change (p>0,05). It also showed that haemoglobin and haematocrit substances in female rats were normal and did not significantly change (p>0,05). Erythrocytes, MCV, MCH, and MCHC in female rats indicated significant change (p<0,05), but they were still in normal ranges.Conclusion: It could be concluded that administration of the combination of extracted meniran and pegagan was not toxic to haematology of the rats in all doses.